2006
DOI: 10.1128/jvi.00967-06
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus B1R Kinase Interacts with JIP1 and Modulates c-Jun-Dependent Signaling

Abstract: Viruses have to adjust to the host cell to guarantee their life cycle and survival. This aspect of the virus-host cell interaction is probably performed by viral proteins, such as serine-threonine kinases, that are present early during infection. Vaccinia virus has an early Ser-Thr kinase, B1R, which, although required for successful viral infection, is poorly characterized regarding its effects on cellular proteins, and thus, its potential contribution to pathogenesis is not known. Signaling by mitogen-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
(77 reference statements)
1
19
0
Order By: Relevance
“…Both H5R and B1R co-localize as punctate sites in the cytoplasm that are precursors to sites of viral DNA synthesis (Domi and Beaud, 2000). Cellular proteins are also phosphorylated by this kinase including p53, which results in the ubiquitination and degradation of p53 (Santos et al, 2004), and other cellular signaling pathways related to cellular stress (Santos et al, 2006). The B1R kinase also inhibits CD1d-mediated antigen presentation and antagonizes an important innate immune response (Webb et al, 2006).…”
Section: Potential Molecular Targets In Orthopoxvirus Replication mentioning
confidence: 99%
“…Both H5R and B1R co-localize as punctate sites in the cytoplasm that are precursors to sites of viral DNA synthesis (Domi and Beaud, 2000). Cellular proteins are also phosphorylated by this kinase including p53, which results in the ubiquitination and degradation of p53 (Santos et al, 2004), and other cellular signaling pathways related to cellular stress (Santos et al, 2006). The B1R kinase also inhibits CD1d-mediated antigen presentation and antagonizes an important innate immune response (Webb et al, 2006).…”
Section: Potential Molecular Targets In Orthopoxvirus Replication mentioning
confidence: 99%
“…VV has the ability to bind cells and activate cellular mitogen-activated protein kinases (MAPK) including p38 MAPK [38], JNK [39], and ERK [40, 41], leading to permissive virus replication in a variety of diverse cell lines. Experimental studies using A31 cells (a clone derived from mouse Balb/c 3T3 cells) have demonstrated that VV triggers a sustained activation of MAPK/ERK1/2 and protein kinase A at an early stage of infection and whose activation are required for VV multiplication [41].…”
Section: Introductionmentioning
confidence: 99%
“…38,45 This proapoptotic protein Bax forms pores in the outer mitochondrial membrane which helps in the releasing of cyt c. 46 As Tat-JBD could inhibit the activation of JNK, we showed that treatment of the peptides inhibited the phosphorylation of Bcl-2 proteins, increased the interaction of Bcl-2 with Bax, prevented Bax translocation to mitochondria, and attenuated the release of cyt c and caspase-3 activation. 14,19,39,42 This suggests that the mitochondriadependent apoptosis pathway mediated by JNKs activation is also involved in dopaminergic neuronal apoptosis induced by MPTP-injury.…”
Section: Discussionmentioning
confidence: 96%
“…12,13 The JNK-binding domain of JIP-1 (JBD) is located at residues 127-282, the N terminus of the protein. 14 Eilers's 15 results showed overexpression of JBD can inhibit JNK activation and reduce the apoptosis induced by the withdrawal of nerve growth factor in PC12 cells. Apoptosis was also reduced or prevented by overexpression of the JBD in the insulin-secreting cells or sympathetic neurons.…”
mentioning
confidence: 99%